Dryland Skate Drills
Like classic skiing, good power application in skating depends upon good body position. However, the issue is complicated in skating by the introduction of another plane of motion. Power in skating is generated as the product of a lateral separation of the contact point (ski on the snow or pavement) from the center of mass. The key to fast skating is a long power application, which means a long separation of contact point and center of mass. In order for this long stride to effectively produce power, alignment is critical. The goal in a single skate stride is to load the skating leg and ski in a way that encourages the ski to keep moving, and then to unload it in a way that creates acceleration. This process requires the efficient transfer of potential energy from the body to the ground. The skating leg and ski are part of a single structural mechanism that is going to produce acceleration very much the way an alpine racer accelerates out of a GS turn. In order for this to work, the leg must be aligned so that it is a structurally sound conduit for potential energy. Common alignment problems in skating result in a knocked-knees or collapsed ankles. Under these circumstances potential energy will be wasted on soft tissue around these joints, and will not produce acceleration. Alignment problems are often wrongly attributed to weak musculature or joints. In fact, most alignment problems in the legs are a product of parallel articulation of the upper leg at the hip joint. Most of what we do every day demands parallel articulation, including walking and running. In order for the entire leg to be aligned in the direction of the ski, it must be turned-out from the hip, and must remain turned-out as power is applied. This requires turned-out articulation of the hip joint. Furthermore, to avoid twisting the upper leg back into parallel articulation during the power application, the hips and trunk should be oriented down the track, NOT along the ski. If the entire body is aligned along the ski, as soon as the weight is shifted toward the other ski, the alignment will change, and the effectivenes of power application through the skating leg will be comprimised. There should be enough flexibility in the hips for the legs to work independently of the pelvis, and independently of each-other.